KARAKTERISASI PLANLET VANILI (Vanilla planifolia Andrews) HASIL SELEKSI IN VITRO DENGAN ASAM FUSARAT TERHADAP Fusarium oxysporum f. sp. vanillae - , Endang Nurcahyani, Dra., M.Si.; , Prof. Dr. Issirep Sumardi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The most production constrain on Vanilla planifolia plantation recently has been caused by foot rot disease that later influence in decreasing the yield product. This disease is caused by Fusarium oxysporum f. sp. vanillae (Fov). So far, the disease has not been successfully prohibited although some experiments had been conducted. The use of foot rot resistant cultivar has been introduced, which has high yield expected as one alternative method for controlling this disease. A resistant vanilla plantlet to Fov has been initiated by in vitro selection on medium containing fusaric acid (FA) on different concentration. The goals of research were to study and determine of: 1) The proper combination of 2,4-D and NAA for callus initiation and shoot development from shoot tip explants, along with proper concentration of BAP for shoots initiation from nodal explant